Organization Theory & Design, 13th Edition - Richard L. Daft (Cengage Learning, 2020)
Introduce your students to the most progressive thinking about organizations today as acclaimed author Richard Daft balances recent, innovative ideas with proven classic theories and effective business practices. Daft's best-selling ORGANIZATION THEORY AND DESIGN presents a captivating, compelling snapshot of contemporary organizations and the concepts driving their success. Recognized as one of the most systematic, well-organized texts in the market, the 13th edition of ORGANIZATION THEORY AND DESIGN helps current and future managers prepare for the challenges of today's business world. The new edition features important revisions, including a new chapter on Designs for Social Impact: Dual-Purpose Organizations and a new chapter on Designs for Digital Organizations and Big Data. Other new topics include Reverse Innovation, Artificial Intelligence, Social Network Analysis and Holacracy Team-Based Structure. In addition, the text continues its tradition of incorporating the most current examples and research alongside time-tested principles. Students see how many of today's well-known organizations have learned to cope and even thrive amidst a rapidly changing, highly competitive international environment. Featured organizations include Facebook, Uber, Amazon, Disney/Pixar, Southwest Airlines, Barnes & Noble, and Cisco Systems and dozens of other companies, many from other countries. Organization studies, proven cases, and illustrations provide the insights necessary to better understand modern organizations, while new and proven learning features give your students opportunities to apply concepts and refine their personal business skills and insights.